Implementing civic education in institutions of formal adult education - Anna KŁAWSIUĆ-ZDUŃCZYK (Edukacja Ustawiczna Dorosłych)
Official analysis describes Polish society as passive, having low levels of civic awareness and social trust, with lack of wide civic education and small openness of institutions to citizens. This diagnosis forces one to think about the conditions of civic education in Poland. This paper contains an analysis of main institutions of formal adult education. An attempt will be made to answer the question to what extent and what kind of civic education related information is transmitted in main institutions of formal adult education.